Primary adenocarcinoma of trachea – looking beyond a normal chest radiograph: A case report (Indian Journal of Case Reports, 2019)
Primary tracheal growths are very rare with an incidence of less than 1%. Presenting with non-specific symptoms, these neoplasms can be difficult to diagnose at earlier stages. We describe the case of a 68-year-old male patient who had shortness of breath, dry cough, and a normal chest radiograph. Absence of clinical improvement following treatment based on an initial diagnosis of asthma prompted further diagnostic interventions that suggested a possible diagnosis of a tracheal tumor. Cytology of bronchial lavage sample confirmed the diagnosis of tracheal adenocarcinoma. The patient was referred to a cancer center for palliative stenting. The presenting case report stresses the point that there are some pulmonary illnesses that may present with normal chest radiographs. Most of these patients may initially be treated as cases of asthma or acute bronchitis. Persistence of symptoms despite therapy must prompt a further diagnostic workup for alternate conditions like localized airway obstruction.